ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA CV BENGKEL BUNGA HARAPAN DI KABUPATEN BERAU - Sayugo Adi Purwanto (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Ilmu Ekonomi (STIE) Pontianak, 2018)
Determination of capital structure is very important for companies and parties outside the company such as creditors and investors because it is very basic and has a long-term impact. One important consideration that must be considered carefully before determining the company's capital structure is the consideration of the amount of capital costs from all funds / capital used by the company. In determining the capital structure must be able to reflect the balance or comparison between foreign capital and own capital that is best in a company influenced by many factors, including: asset structure and earning stability. CV Bunga Harapan Workshop in Berau District in the face of tight business competition must be able to establish an optimal capital structure. This is because the capital structure is an important problem for every company, because the good and bad capital structure will have a direct effect on the company's financial position. The initial observation shows CV Bunga Harapan Workshop in Berau District does not understand the problem of the capital structure.The purpose of this study was to determine the effect of asset structure and earnings stability on the capital structure on CV Harapan Bunga Workshop in Berau District. Data analysis tools used were normality test, multicollinearity test, autocorrelation test, multiple linear regression analysis, determination coefficient, t test and F test. The results of this study conclude that the structure of assets and earnings stability have a significant effect on the capital structure of CV Bunga Harapan Workshop in Berau District. This is evidenced by the results of the F test where F-count is greater than F-table (21.115> 4.74) and significant value 0.001 <0.05. The asset structure has a significant effect on the capital structure at CV Bunga Harapan Workshop in Berau District. This is evidenced by the results of the t test where -t count is smaller than -t-table (-3,078 <-2,365) and significant value (0,000) smaller than 0,05. Earning stability has a significant effect on the capital structure at CV Bunga Harapan Workshop in Berau District. This is evidenced by the results of the t test where t-count is greater than t-table (2.975> 2.365) and a significant value (0.021) which is smaller than 0.05.